2021
DOI: 10.9734/ajeba/2021/v21i1830495
|View full text |Cite
|
Sign up to set email alerts
|

Public Education Funding and Economic Growth IN Nigeria; ARDL-VECM and Causal Inference Approach

Abstract: Considering the enormous impact of poor standard of educational system in Nigeria over the years, the study investigated the effects of public education funding on economic growth in Nigeria from 1985 to 2019. The paper used secondary data sourced from both Central Bank of Nigeria Statistical Bulletin and World Bank’s Development Indicators 2019. The paper employed Auto-Regressive Distributed Lag co-integration, Error correction mechanism and granger-causality tests as technique for data analysis. The ARDL bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 6 publications
3
10
0
1
Order By: Relevance
“…This contributes to boosting the net volume of exports and economic growth via the multiplier effect (Shakeel et al, 2014). The positive effect of energy consumption on economic growth in South Asian economies obtained from this study finding is consistent with M. S. Islam and Ali (2011); Alam et al (2012); Ouedraogo (2013); Mahalik and Mallick (2014); Marques and Fuinhas (2016); Esen and Bayrak (2017); Iheanacho (2018); Shahbaz et al (2018a); Sarker et al (2019); Topcu et al (2020); H. S. Ali et al (2020); M. M. Islam and Islam (2021) and Udemba et al (2021), who mainly established these findings based on the causal analysis in the context of different countries. This study finding is contradictory with Joyeux and Ripple (2007); Jumbe (2004); Lee (2005); Squalli (2007); Carfora et al (2019) and Sharma et al (2021).…”
Section: Empirical Findings and Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This contributes to boosting the net volume of exports and economic growth via the multiplier effect (Shakeel et al, 2014). The positive effect of energy consumption on economic growth in South Asian economies obtained from this study finding is consistent with M. S. Islam and Ali (2011); Alam et al (2012); Ouedraogo (2013); Mahalik and Mallick (2014); Marques and Fuinhas (2016); Esen and Bayrak (2017); Iheanacho (2018); Shahbaz et al (2018a); Sarker et al (2019); Topcu et al (2020); H. S. Ali et al (2020); M. M. Islam and Islam (2021) and Udemba et al (2021), who mainly established these findings based on the causal analysis in the context of different countries. This study finding is contradictory with Joyeux and Ripple (2007); Jumbe (2004); Lee (2005); Squalli (2007); Carfora et al (2019) and Sharma et al (2021).…”
Section: Empirical Findings and Discussionsupporting
confidence: 90%
“…There is a significant long-term positive impact of energy consumption on income growth whereas bilateral causal relations are detected among energy consumption, globalization, and income growth in Nigeria (Iheanacho, 2018). The positive correlation between globalization and energy use is found in the perspective of the Netherlands and Ireland (Shahbaz et al, 2018b).…”
Section: Literature Reviewmentioning
confidence: 94%
See 2 more Smart Citations
“…Marques et al (2017) found a significantly positive effect of economic, political and social globalization on the "ENC-economic growth" link for a panel of 43 countries. Iheanacho (2018) investigated the association between globalization, energy use and economic progress in Nigeria using data for the 1975-2011 period and an ARDL technique and reported a feedback association between globalization and energy use. Shahbaz et al (2018) applied the Quantile Autoregressive Distributed Lag model for two European economies, that is, The Netherlands and Ireland, and found that globalization is related to ENC positively in the long run.…”
Section: Globalization and Energy Consumptionmentioning
confidence: 99%